Methotrexate-Polymer Nanocomposites for Targeted Pulmonary Drug Delivery - Aseel Khaled Mohammad AL-Sarayrah; Samer Hasan Hussein-Al-Ali; Mike Khalil Haddad; Dalia Kalil (Universitas Gadjah Mada, 2024)
Nanocomposite formulation is a suitable technology that enables the development of successful dry powder inhalers. The methotrexate (MTX) and polyamide-disulfide (polymer) were used as a model to form MTX-polymer nanocomposites. Different amounts of the independent variable, MTX (0.025 and 0.050 g), polymer (0.05 and 0.01 g), pH (6.7 and 11.3), and across-linker ferric chloride (FeCl3) (0.05 and 0.10 g) were used. The loading efficiency and particle size were dependent variables. The optimized formula can be obtained with the highest loading efficiency and optimum particle size. This formula can be collected by using 0.025 g of drug, 0.079 g of polymer, 0.050 g of FeCl3, and pH = 6.7. The release of MTX from the nanocomposites occurs in two release steps; the first release step starts from the beginning up to 60 min, followed by a continuous release phase within 60 min. The results of the NGI analysis demonstrated that 28.1% of the nominated dose in each puff reached the lower parts of the respiratory system, an indication that the nanocomposites can be used in the delivery of MTX as a respiratory system.